Prevalence and sociogeographical inequalities of violence against women in Ecuador: a cross-sectional study - Agnes Edeby; Miguel San Sebastián (BMC, 2021)
Abstract Background Violence against women (VAW) is a vast public health problem in Latin America. The aim of this study was to determine the prevalence of violence against women and to assess its sociogeographical inequalities in Ecuador during 2019. Methods This cross-sectional study used data from a national survey conducted in 2019 (n = 17,211) among women aged 15 years and over. Independent variables included age, marital status, education, ethnicity, place of residence and region. The chosen outcomes were lifetime experience of total violence, sexual violence, physical violence, psychological violence and economic violence. Frequency tables were first calculated, and then crude and adjusted regression models estimating risk differences and their 95% confidence intervals were computed. Results Nearly two-thirds (64.86%) of the participating women had experienced some form of violence during their lifetime, mainly psychological violence (56.92%). The second most prevalent type of violence was physical (35.44%) closely followed by sexual (32.67%). Almost one-fifth (16.38%) stated to have experienced some form of economic violence. Physical and psychological violence were more common among women aged 26-35 and less among older women. All forms of violence were more often reported among women with no education except for sexual violence, which was more frequent among those with higher education. Physical, psychological and economic violence were more often reported by those living with a partner, being married or divorced/separated. Sexual violence was associated with those belonging to a non-indigenous ethnic group, while all types of violence were more common among those living in an urban setting (except physical violence), in the Highlands or in the Amazon region. Conclusions Our study showed that VAW is a common event in Ecuador and identified several sociogeographical inequalities that varied depending on the type of violence. VAW was more common among the younger age groups, those with low education, those living with a partner or being divorced/separated, or residing in an urban setting, in the Highlands or in the Amazon. Further studies including more social factors and a continuous monitoring of VAW are recommended. Current policies and laws to protect women need to be expanded and effectively implemented to reduce VAW in the Ecuador.